2018
DOI: 10.5603/gp.a2018.0021
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gynaecologist in the promotion and maintenance of oral health during pregnancy

Abstract: Objectives: The aim of the study was to assess routine dental examination attendance of pregnant women and a possible impact of gynaecological referrals on the attendance rate. Material and methods:An electronic survey was conducted that was inclusive of women up to 5 years following delivery. The questions related to socio-demographic data, the course of pregnancy and childbirth, and visits to dental office during pregnancy. For statistical analysis, the authors utilized the chi-square test, Spearman's rank c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…This is concerning since habits and attitude toward oral health are set early in life, hence physicians and OBGYNs attending young women have an opportunity to capitalize on this by integrating oral health as an essential component of reproductive health during the counseling of young women. It has been shown that lack of counseling is a major factor in preventing adequate dental care access and that referral from a gynecologist can increase the frequency of dental appointments . In a population‐based study among pregnant women in California, it was found that college graduates were more likely to report attitudinal barriers and lack of perceived need for dental care during pregnancy as compared to more disadvantaged women …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is concerning since habits and attitude toward oral health are set early in life, hence physicians and OBGYNs attending young women have an opportunity to capitalize on this by integrating oral health as an essential component of reproductive health during the counseling of young women. It has been shown that lack of counseling is a major factor in preventing adequate dental care access and that referral from a gynecologist can increase the frequency of dental appointments . In a population‐based study among pregnant women in California, it was found that college graduates were more likely to report attitudinal barriers and lack of perceived need for dental care during pregnancy as compared to more disadvantaged women …”
Section: Discussionmentioning
confidence: 99%
“…Using methods recommended by NCHS, the analysis was weighted to provide estimates at the level of the US population . The 2‐year exam sample weights were used to construct weights across the three data cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Badania ankietowe 3439 Polek w okresie 5 lat od porodu pokazały, jak ważna jest rola lekarza prowadzącego ciążę w zwiększaniu odsetka kobiet ciężarnych korzystających z opieki stomatologicznej -skierowanie przez ginekologa znacząco zwiększało szanse zgłoszenia się do lekarza dentysty (OR = 5,20 (4,05-6,67); p < 0,001). Jeszcze większą skuteczność wykazano przy jednoczesnym żądaniu od lekarza dentysty pisemnej odpowiedzi zwrotnej o stanie zdrowia jamy ustnej (OR = 2,19 (1,66); p = 0,003) (17,18). Równie ważna jest edukacja prozdrowotna kobiet, która wpływa na zmianę niewłaściwych zachowań pacjentek sprzyjających próchnicy zębów oraz chorobom przyzębia i błony śluzowej jamy ustnej zarówno u kobiet, jak i u przyszłego potomstwa.…”
Section: Wynikiunclassified
“…Udzielanie informacji na temat zasad dotyczących profilaktyki przeciwpróchnicowej oraz chorób przyzębia powinno spoczywać na lekarzu dentyście lub higienistce stomatologicznej, natomiast wprowadzenie w życie i stosowanie ich w codziennych zabiegach zależą od stopnia zrozumienia problemu oraz sumienności pacjentek (11)(12)(13). Wśród czynników wpływających na zgłaszalność się do dentysty na świecie wymieniane są: regularne korzystanie z opieki stomatologa przed ciążą, poziom wiedzy o zdrowiu jamy ustnej i jego wpływie na przebieg ciąży i dziecko oraz poczucie, że leczenie stomatologiczne w ciąży jest bezpieczne (14)(15)(16)(17)(18).…”
Section: Wstępunclassified
“…Some organizations, such as the American Congress of Obstetricians and Gynecologists and the American Dental Association, report that it is possible for pregnant women to take dental imaging radiographs during any trimester of their pregnancy period. However, they assume that this is possible only by using and applying the measurements of radiation protection to hold the dose amount as low as reasonably achievable (ALARA) [ 1 – 7 ]. The shortage of knowledge relating to the protection of dental radiographs prevents pregnant women from searching for dental pathologies for treatment.…”
Section: Introductionmentioning
confidence: 99%